(3eNJUQ cJGH aj GdUfYI ddeLQjWjs - (3GdGfWGcj GdMfaj, edG YQH, eMeO Hf eMeO Hf MeRI Hf YhV, (B938 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdefaQO HGdCMOjI bGd GdQFjS GdaGVd GdeLQjWj deG QCjJ GdYdhe GdObjbI bO eGJJ hde jHb ef Yde GdUfYI EdG GSegG CMHHJ Cf CMjj eG eGJ hCfG GdCfWGj CMHHJ Cf CdNU cdGeg s
(3BNQgG (B:s
(3hGdRFHb deG Je WHNJg HGdMQGQI GSJe GdcHQjJ GdPj aj HGWf GdRFHb GdjHS ef OGQI GdWHGN Edi faSg HbhdI hTOI jHSg aGJUd Hjf GdfGQ aGMeQ GdLQe hUGQ PgHG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\640s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdcjejGA hGdWHjYjGJs